2019
DOI: 10.31083/j.jin.2019.04.1168
|View full text |Cite
|
Sign up to set email alerts
|

Purkinje cells of vestibulocerebellum play an important role in acute vestibular migraine

Abstract: J o u r n a l o f I n t e g r a t i v e N e u r o s c i e n c e

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 51 publications
1
9
1
Order By: Relevance
“…There is also evidence of otolithic pathway abnormalities in individuals with VM [34]. It is also suggested that Purkinje cells in the paraflocculus could be inhibited after the occurrence of a migraine episode, which may be an important factor leading to vestibular migraine [35]. Magnetic resonance studies have shown an increased thalamic activation in VM patients during vestibular stimulation compared to healthy controls, as well as grey matter volume abnormalities of nociceptive and multisensory vestibular brain areas [36,37].…”
Section: Pathophysiology Of Vmmentioning
confidence: 99%
“…There is also evidence of otolithic pathway abnormalities in individuals with VM [34]. It is also suggested that Purkinje cells in the paraflocculus could be inhibited after the occurrence of a migraine episode, which may be an important factor leading to vestibular migraine [35]. Magnetic resonance studies have shown an increased thalamic activation in VM patients during vestibular stimulation compared to healthy controls, as well as grey matter volume abnormalities of nociceptive and multisensory vestibular brain areas [36,37].…”
Section: Pathophysiology Of Vmmentioning
confidence: 99%
“…Brain imaging studies have reported that the cerebellar sodium concentration and functional connectivity to the insula or anterior cingulate cortex were altered in animal migraine models induced by nitroglycerin or inflammatory soup ( 53 55 ). The firing rate of Purkinje cells in the rat paraflocculus was decreased in an animal model induced by trigeminal stimulation ( 56 ), and the organization of parallel fibers to Purkinje cell synapses was abnormal in familial hemiplegic migraine type 1 mouse models ( 57 , 58 ). There are also preclinical behavioral studies investigating the role of the cerebellum in pain modulation ( 41 43 , 59 – 64 ).…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, this is the first preclinical cerebellar migraine study looking at behavioral outcomes. Indeed, there have been few animal studies looking at imaging and electrophysiological links between the cerebellum and migraine (87)(88)(89)(90)(91)(92). Brain imaging studies have reported that the cerebellar sodium concentration and functional connectivity to the insula or anterior cingulate cortex were altered in animal migraine models induced by nitroglycerin or inflammatory soup (87)(88)(89).…”
Section: Discussionmentioning
confidence: 99%
“…Brain imaging studies have reported that the cerebellar sodium concentration and functional connectivity to the insula or anterior cingulate cortex were altered in animal migraine models induced by nitroglycerin or inflammatory soup (87)(88)(89). The firing rate of Purkinje cells in the rat paraflocculus was decreased in an animal model induced by trigeminal stimulation (90), and the organization of parallel fibers to Purkinje cell synapses was abnormal in familial hemiplegic migraine type 1 mouse models (91,92). There are also preclinical behavioral studies investigating the role of the cerebellum in pain modulation (70)(71)(72)(93)(94)(95)(96)(97)(98)(99).…”
Section: Discussionmentioning
confidence: 99%